HUBUNGAN KEBIASAAN OLAHRAGA DENGAN KEJADIAN DISMINORE PADA MAHASISWI ILMU KEPERAWATAN - Romlah Romlah; M.K Fruitasari Fruitasari (JURNAL KESEHATAN INDRA HUSADA, 2022)
Around the world, dysmenorrhea cases have already reached the high level. Data from WHO showed that there were 1,769,425 women (90%) suffering from dysmenorrhea. In the meantime, regular exercise has been known to be able to decrease the risks of dysmenorrhea since it could trigger the secretion of endorphin hormone, which could ease the pains. It is expected that doing regular exercises could decrease the number of dysmenorrhea sufferers. This study aimed at finding out the correlations between exercise habits and dysmenorrhea of nursing science students of Health Science Faculty of Musi Charitas Catholic University Palembang. Analytic survey was used with cross sectional approach. The respondents were 57 nursing science students, out of 131 total populations. They were selected by stratified random sampling method. The data from univariate statistic test showed: 42.1% (24) of respondents had good exercise habits, 57.9% (33) did not have good exercise habits, 61.4% (35) suffered from dysmenorrhea, and 38.6% (22) did not suffer from dysmenorrhea. The result of bivariate statistic test by chi square showed p value 0.001 < 0.05, which meant there were correlations between exercise habits and dysmenorrhea. As a result, the female students were suggested to do exercise regularly to avoid the pains of menstruation.